Coupling pre-mRNA processing to transcription on the RNA factory assembly line - Lee, Kuo-Ming (Landes Bioscience, 2013)
It has been well-documented that nuclear processing of primary transcripts of RNA polymerase II occurs co-transcriptionally and is functionally coupled to transcription. Moreover, increasing evidence indicates that transcription influences pre-mRNA splicing and even several post-splicing RNA processing events. In this review, we discuss the issues of how RNA polymerase II modulates co-transcriptional RNA processing events via its carboxyl terminal domain, and the protein domains involved in coupling of transcription and RNA processing events. In addition, we describe how transcription influences the expression or stability of mRNAs through the formation of distinct mRNP complexes. Finally, we delineate emerging findings that chromatin modifications function in the regulation of RNA processing steps, especially splicing, in addition to transcription. Overall, we provide a comprehensive view that transcription could integrate different control systems, from epigenetic to post-transcriptional control, for efficient gene expression.